Penambahan Fasilitas Pembuatan Surat Nikah Pada Aplikasi Surat Keterangan Desa (SUKET)Di Pemerintah Kabupaten Sragen - Pradana, Rizka Adi; , Helman Muhammad, S.T., M.T (2016)
In conducting its activities, District Government Office of Sragen has been using web-based information system which allows public to access the required information anytime and anywhere. With this system District Government Office of Sragen can expand the range of its services without having to spend much time and cost. One of the application that has been used is called Village Certificate (Surat Keterangan Desa, abbreviated as SUKET). This application, which can be accessed from various village offices within the District of Sragen area, is intended to simplify the making of various kind of certificates. Meanwhile, the administrative process for the making of marriage-related certificates in the District Government Office of Sragen is still conducted manually. The employees record the incoming and outgoing papers in a ledger. This fact brought about the idea on the further development of the SUKET application, by adding facilities for the making of marriage-related certificates. The result is a new application which provides facilities for the making of marriage-related certificates. This application was developed with PHP and MySQL, and designed to be a part of the SUKET application. Hence the existence of this new application also means improvement to the SUKET application.